Olfactory Neuroblastoma: Surgical Treatment Experience of 42 Cases - Cai, Xiao; Peng, Zhouying; Zhang, Hua; Fan, Ruohao; Fang, Yan; Xie, Zhihai (Frontiers in Surgery, 2022)
Objective: Our purposes were to estimating the safety and effectiveness of endoscopic endonasal approach (EEA) and determine if preservation of dura and olfactory bulb could be considered in selected patients. Methods: We retrospectively reviewed patients with a diagnosis of ONB between July 2010 and June 2021 in our institution, and collected demographic data, stage of disease, surgical approach, overall survival (OS) and disease-free survival (DFS) and postoperative complications. Results: The study sample included 42 cases (8 treated for recurrence and 34 initial cases). There were 28 males and 14 females. with a median age 47.19 years. The mean beginning to treatment months and follow-up time was 8.91 and 51. 32 of the patients had the unilateral lesion and the rest had bilateral. Patient symptoms are predominantly nasal, and thhere were 4 patients without any symptom. The modified Kadish staging was were A, B, C, D with 3 patients, 14 patients, 17 patients, 8 patients respectively. 5 patients had cervical lymph node metastasis while no patients had distant metastasis according to the preoperative examination. There were 38 patients used EEA, while 3 used the cranioendoscopic approach and 1 the open craniofacial approach (CFA). The 5-year OS rate and DFS rate were 89.1% and 79.2%, respectively. The 2-year OS rate and DFS rate were both 89.1%. The overall surgical complications incidence was 9.52% (One cerebrospinal fluid rhinorrhea, one cervical hematoma and two epileptic seizure). Conclusion: The present results support the importance of the earlier treatments for advanced ONB and the thesis that it is safe and efficacious to treat ONBs via EEA and preservation of dura can be considered in parts of selected patients (without skull base involvement and being able to have post-operative comprehensive therapy).